A presença das relações de gênero no currículo da escola pública: opiniões de professores e professoras. - Nascimento, Marcelo Oliveira Do [UNIFESP] (2019)
This research aimed to listen and analyze the opinion of teachers about the relevance they attribute to the presence of issues related to gender issues, those explained in the curriculum and those that emerge from everyday events and that imply the need to debate the theme at school. The survey was conducted among professionals from municipal public schools in the eastern part of the city of São Paulo that serve young people in the middle school stage. The municipal public network has 8 schools that serve young people in this stage of education in the city, and our research was carried out in 3 of them that are allocated in the east zone. Our listening was through the focus group technique, with 2 meetings in each unit, aimed at investigating the assessment of gender relations by school actors and their perceptions about the latest national and municipal education plan. And can enlarge the understanding of ideas, concepts and considerations that teachers have about the concept of gender.